2009
DOI: 10.1039/b908997g
|View full text |Cite
|
Sign up to set email alerts
|

Single-walled hollow nanospheres assembled from the aluminogermanate precursors

Abstract: Ordered single-walled hollow aluminogermanate (ALGE) nanospheres (NSs) with average monodisperse diameters of 5 nm have been synthesized for the first time using simple pH control. This involved basification of the ALGE precursors (having an Al/Ge ratio of 1.33) to a pH value of 13, followed by immediate acidification to a pH value of 9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…This also accompanied by a decrease of the vibration at 690 cm −1 and the appearance of a new peak located at 745 cm −1 (arrows in Figure 4). These features were attributed previously to a specific mode either for aluminogermanate single-walled INTs formed when decreasing the hydrolysis ratio [35] or aluminogermanate nanospheres synthesized in basic conditions [33]. In the present case, the absorption band observed at 745 cm −1 is highly pronounced for R' = 0.9 for which we have observed the presence of single-walled nanotubes based on WAXS experiments, but it also remains significant for the lowest value of R' while only plate-like structures are observed (Figure 2a).…”
Section: Structural Properties Of Final Productssupporting
confidence: 52%
See 1 more Smart Citation
“…This also accompanied by a decrease of the vibration at 690 cm −1 and the appearance of a new peak located at 745 cm −1 (arrows in Figure 4). These features were attributed previously to a specific mode either for aluminogermanate single-walled INTs formed when decreasing the hydrolysis ratio [35] or aluminogermanate nanospheres synthesized in basic conditions [33]. In the present case, the absorption band observed at 745 cm −1 is highly pronounced for R' = 0.9 for which we have observed the presence of single-walled nanotubes based on WAXS experiments, but it also remains significant for the lowest value of R' while only plate-like structures are observed (Figure 2a).…”
Section: Structural Properties Of Final Productssupporting
confidence: 52%
“…Increasing or decreasing the hydrolysis ratio can lead to nanotubes with variable amount of defects or to the hindering of the formation of nanotubes for R < 1.5 and R > 2.5 [32]. It was also suggested that, under basic conditions, hollow nanospheres are formed instead of nanotubes when the precursor ratio R' = [Al]/[Ge] is lowered below 2 [33], which is the ratio of Al and Ge atoms within a non-defective Ge-based INT with formula Ge(Al)2O7H4. Finally, while Si-based INTs are singlewalled (SW) nanotubes, germanium-based nanotubes are obtained as single-walled (SW) or doublewalled (DW) nanotubes depending on the initial concentration of aluminum C[Al] (Figure 1b) [34,35], the latter having an internal diameter of 1.5 nm for an external diameter of 4.3 nm and a limited average length of ~ 20 nm [36].…”
Section: Introductionmentioning
confidence: 99%
“…5 It indicates strongly that Ge-incorporation should play a crucial role in stabilizing the akaganeite structure. The band at 858 cm À1 and a weak shoulder at about 950 cm À1 for the 1000 C heated sample may be assigned to the Ge-O stretching, 19 which would be due to the appearance of Ge-oxide (Fig. 7).…”
Section: Thermal Propertiesmentioning
confidence: 99%
“…DFT simulations have been coupled to experiments to propose a mechanism for the selection of the two types of curvature (spherical and tubular). It is concluded that the ions and pH seems to play an important role (Abidin et al, 2007;Bac et al, 2009). The use of Si-CH 3 groups for the internal surface of the ILS nanominerals maintains a spontaneous curvature without the formation of H bond network and electrostatic interactions.…”
Section: Introductionmentioning
confidence: 97%